Relationship Between Nurse Caring and Parents Anxiety Level in Children Who Has Hospitalized Based on Approach Swanson Theory - Intan Nurani; Achmad Dafir Firdaus; Rahmawati Maulidia (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Parents have a very supportive role for chidren. Especially in children who are experiencing hospitalization. Hospitalization can have an impact on both the children and the parents. In general, anxiety is one of the effects of hospitalization on both children and parents. So that the nursing care needed t address hospitalization is not only focused on children but also on parents. Comprehensive nursing care is an indicator of professional service quality by nurses which can be demonstrated by caring behavior. The purpose of this research is to find out the relationship between nurse caring and parental anxiety levels in children experiencing hospitalization is based on the swanson theory approach. This research is a literature review using several literature search strategies, namely using the PICOS, keywords used nurse caring, parental anxiety, child hospitalization and the database used was Garuda, Google Scholar, ProQuest and PubMed. There is a significant relationship between nurse caring and the level of anxiety of parents whose children are hospitalized. Nurse caring based on the Swanson theory is a caring behavior that can be nurtured and evaluated at any time. So that the caring of nurses based on Swanson theory is expected to reduce parental anxiety levels in chidren experiencing hospitalization. And furthermore can have positive effects such as accelerating recovery, shortening hospitalization and increasing patient and family satisfaction.